Analisis Pengaruh Dana Syirkah Temporer dan Efisiensi Operasi Terhadap Profitabilitas Bank Syariah - Muhammad Noval; Lisda Aisyah (Jurnal Ilmiah Ekonomi Islam, 2021)
The purpose of this research is to examine the effect of Temporary Syirkah Fund and Operational Efficiency on Sharia Bank Profitability. Indicator of Syirkah Temporary Fund under study is the amount of public savings funds in Sharia Bank with Mudharabah contract. Operating Efficiency uses the ratio indicator of Operating Expense on Operating Revenue (BOPO). Then, Sharia Bank Profitability is the calculation of Return On Asset Ratio (ROA). The research is conducted by quantitative methods using secondary data. The secondary data comes from quarterly reports from Sharia Bank in Indonesia. The population of this research is Sharia Bank in Indonesia, and then the sample is taken based on purposive sampling with the criteria of five Sharia Bank with the largest assets, to obtain the sample as much as 60 quarterly report of Sharia Bank. This study used regression analysis with significant test of simultaneous parameter (F - test) and significant test of individual parameter (t - test). The result of the hypothesis test indicates that simultaneously and partially Temporary Syirkah Fund and Operational Efficiency affect to Sharia Bank Profitability in Indonesia, calculated by ROA Ratio, and Operating Efficiency have bigger influence to Sharia Bank Profitability compared to Temporary Syirkah Fund.